The race to a COVID-19 vaccine: opportunities and challenges in development and distribution - Burgos, Rodrigo M; Badowski, Melissa E; Drwiega, Emily; Ghassemi, Samaneh; Griffith, Nikki; Herald, Fischer; Johnson, Mikayla; Smith, Renata O; Michienzi, Sarah M (Drugs in Context, 2021)
The unprecedented toll of severe acute respiratory syndrome coronavirus 2, the virus responsible for coronavirus 2019 disease (COVID-19), jumpstarted the race towards the development and distribution of effective treatment and prevention options. With an urgent need to slow viral transmission, lessen disease severity, and reduce mortality, biopharmaceutical companies rapidly began investigating potential COVID-19 vaccinations. While typical vaccine development can take upwards of 10-15 years, COVID-19 vaccines were developed in less than a year after the identification of COVID-19. To accomplish this feat, clinical development, manufacturing scale-up and distribution are occurring in parallel for the four COVID-19 vaccine front-runners. This remarkable opportunity will forever change the drug development process and would not be possible without tremendous dedication from the public and private sectors, researchers, and clinical trial volunteers. However, many challenges still lie ahead. Comprehensive plans for equitable vaccine education, distribution, administration and post-marketing surveillance must be implemented successfully to overcome vaccine hesitancy, supply-chain obstacles and healthcare provider shortages in an already overburdened healthcare system. We are moving forward at a remarkable pace but worldwide immunity through vaccination will take time to achieve. Thus, current prevention efforts of masking, hand hygiene and social distancing must remain in effect for the foreseeable future. We must remain diligent and not fatigue in our efforts. Ending the COVID-19 pandemic cannot rest on the promise of vaccination alone - it will require a continued, robust and multi-faceted approach to disease treatment and prevention.